Postprandial Plasma Glucose Responses And Glycaemic Indices Of Different Forms Of A Large Sago Meal. - Ghosh, Prof.Madya Ashok Kumar; Mat Easa, Prof.Madya Azhar; Singh, Prof.Madya Rabindarjeet (Persatuan Pemakanan Malaysia, 2005)
The aim of the study was to determine the postprandial plasma glucose responses and glycaemic indices of three different physical forms of a sago meal. Twelve healthy subjects consumed in random order, three white bread meals and three sago meals (sago porridge, sago paste and sago gel) on separate days at least 1 week apart after an overnight fast.